UN-MASKING ON SCREEN POLITENESS IN HACKSAW RIDGE MOVIE - Ramadan Adianto Budiman; Febrian Febrian (Universitas Sebelas Maret, 2023)
This research was conducted by analyzing every utterance is contained in the Hacksaw Ridge film subtitle and its translation which represents the bald on record politeness strategy. This study not only aims to describe how the bald on record politeness strategy contained in the Hacksaw Ridge film subtitle from English to Indonesian but also researchers wants to examine the role of translators when faced with the audio-visual field, which has various rules that are not easy for professional translators to follow. In the Hacksaw Ridge film, the researcher found that the majority of utterances representing bald on record politeness strategies were translated using establish equivalent, variation, implicit, explicit, reduction, borrowing, and discursive creation techniques. In bald on record translations that apply the usual equivalent translation technique, it produces translations that are accurate, acceptable, and have a high level of legibility. In addition, the role of translators in the audio-visual field cannot decide for themselves how the translation is applied to audio-visual media. Of course, A translator will be interrupted by the subtitle editor and also the owner of the audio-visual media provider company that uses the translator's services.